Hubungan Pembinaan Orang Tua dan Pembinaan Siswa dengan Jiwa Kepemimpinan Siswa Di SMP Muhammadiyah 1 Bogor - Herlina Herlina; Muhyani Muhyani; Zahrotunni'mah Zahrotunni'mah (Pusat Penerbitan Universitas (P2U) Unisba, 2018)
This study aims to determine the relationship of parental guidance and coaching students with the leadership spirit of students in Muhammadiyah 1 Junior High School, Bogor City. This study uses quantitative methods. The design of this study is correlation research. The subjects in this study were students of Bogor 1 Muhammadiyah Middle School whose population amounted to 430 students with a total sample of 25% of the total population of 125 students. Data collection was carried out using questionnaire instrument 3 variable X1, namely Parenting and X2 variables, namely student coaching in school and variable Y, namely the soul of Vain leadership. To find out the relationship between parenting and fostering students with the leadership spirit of students in school, using the multiple correlation formula. Multiple Correlations. The results of the correlation coefficient between the three variables namely the magnitude of r_count (ie = 0.235) the amount between 0.41-0.60 means that the positive correlation between variables X1, X2 and Y includes a weak correlation in parental education and coaching in schools with a leadership spirit. So it can be concluded that based on data analysis obtained from this study there is a significant correlation between parental exemplary and religious fostering in schools with a religious awareness of students at the City of Bogor 1 Junior High School. Keywords: Fostering Parents, Guiding Students, Student Leadership Spirit. Abstrak Penelitian ini bertujuan untuk mengetahui hubungan pembinaan orang tua dan pembinaan siswa dengan jiwa kepemimpinan siswa di SMP Muhammadiyah 1 Kota Bogor. Penelitian ini menggunakan metode kuantitatif. Rancangan penelitian ini adalah penelitian korelasi. Subyek dalam penelitian ini adalah siswa SMP Muhammadiyah 1 Kota Bogor yang populasinya berjumlah 430 siswa dengan jumlah sampel 25% dari jumlah populasi yaitu 125 siswa. Pengumpulan data yang dilakukan dengan instrument angket 3 variabel X1, yaitu Pembinaan orang tua dan variable X2, yaitu pembinaan siswa di sekolah dan variabel Y, yaitu Jiwa kepemimpinan siawa. Untuk mengetahui hubungan antara pembinaan orang tua dan pembinaan siswa dengan jiwa kepemimpinan siswa di sekola menggunakan rumus kolerasi berganda. Hasil koefisien kolerasi antara tiga variabel Yaitu besarnya (yaitu = 0,235) yang besarnya antara 0,41-0,60 berarti korelasi positif antara variabel X1, X2 dan Y termasuk korelasi lemah dalam pendidikan orang tua dan pembinaan di sekolah dengan jiwa kepemimpinan. Maka dapat disimpulkan bahwa berdasarkan analisis data yang diperoleh dari penelitian ini adalah terdapat korelasi yang signifikan antara keteladanan orang tua dan pembinaan keagamaan di sekolah dengan kesadaran beragama siswa di SMPN 1 Kota Bogor. Kata Kunci: Pembinaan Orang Tua, Pembinaan Siswa, Jiwa Kepemimpinan Siswa.